THE INFLUENCE OF OPERATIONAL INCOME AND LOAD ASSOCIATION, LEVERAGE, AND FIRM SIZE ON EARNING MANAGEMENT - Yosvid, Yosvid (International Journal of Public Budgeting, Accounting and Finance, 2020)
This study aims to analyse the effect of the association between revenue with operating expense, leverage, and firm size on earnings management in manufacturing companies in Indonesia. This study uses data for 2018 and 2017 but for some time series data needed to use data starting in 2014. This study uses market data obtained from financial statements using a sample of 74 companies that meet the sample selection requirements. The data analysis technique used in this research is Multiple Regression analysis with processing using the Statistical Product and Service Solutions (SPSS) program. The results of the simultaneous study cannot show a significant effect of the association between revenue with operating expense, leverage, and firm size on earnings management. The partial test shows that only the leverage variable has an effect on earnings management.